2015
DOI: 10.1103/physrevlett.115.237002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Electronic Structure of Each Ingredient Oxide Layer of High-TcCuprate SuperconductorBi2Sr2<

Abstract: Understanding the mechanism of high transition temperature (Tc) superconductivity in cuprates has been hindered by the apparent complexity of their multilayered crystal structure. Using a cryogenic scanning tunneling microscopy, we report on layer-by-layer probing of the electronic structures of all ingredient planes (BiO, SrO, CuO2) of Bi2Sr2CaCu2O 8+δ superconductor prepared by argonion bombardment and annealing technique. We show that the well-known pseudogap (PG) feature observed by STM is inherently a pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
4
14
0
3
Order By: Relevance
“…2a, we summarize our measurements of the averaged gap magnitudes, ∆ s and ∆ p , as a function of ∆ p,BiO simultaneously acquired on the exposed BiO surfaces. Here ∆ p,BiO and thus the hole carriers are delicately controlled by annealing the samples under ozone flux or UHV [3,4]. The larger energy gap, ∆ p , is found to scale linearly with ∆ p,BiO and bears striking quantitative correspondence in the magnitude (red dashes) and spatial variation (marked by the equal statistical uncertainty) to ∆ p,BiO , further stressing its nature as the gap in Bi-2212 substrates [13].…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…2a, we summarize our measurements of the averaged gap magnitudes, ∆ s and ∆ p , as a function of ∆ p,BiO simultaneously acquired on the exposed BiO surfaces. Here ∆ p,BiO and thus the hole carriers are delicately controlled by annealing the samples under ozone flux or UHV [3,4]. The larger energy gap, ∆ p , is found to scale linearly with ∆ p,BiO and bears striking quantitative correspondence in the magnitude (red dashes) and spatial variation (marked by the equal statistical uncertainty) to ∆ p,BiO , further stressing its nature as the gap in Bi-2212 substrates [13].…”
Section: Methodsmentioning
confidence: 84%
“…Because of asymmetric doping and a peculiar bonding configuration of CuO 2 on the inert BiO surface, we speculate that the total charge transfer is not sufficient to make the whole films superconducting, leading to the formation of two different regions. The situation may be improved by growing CuO 2 on the SrO surface of Bi-2212 [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…同原子层进行直接研究 [47] . [48] 、角分 辨光电子能谱(Angle-Resolved Photoemission Spectroscopy, ARPES) [49] 等都是在BiO层上进行的, 在BiO和 SrO层是绝缘性的前提下 [50] [44] [66,67] . 这些能隙的大小也随空间而变化, 但明显小于(100)面 上的能隙 [47] .…”
Section: 此外 研究者还利用横截面Stm对组成铜氧化物的不unclassified
“…关于铜氧化物超导体在费米面上出现能隙节点的 d波配对对称性, 已经被许多体或者表面敏感的实验技 术所研究, 其中包括表面敏感的扫描隧道显微镜 (Scanning Tunneling Microscopy, STM)和扫描隧道谱 (Scanning Tunneling Spectroscopy, STS)研究 [43] . 以 [43][44][45][46] .…”
unclassified
“…The layer-by-layer probing of these layered superconductors is extremely important as illustrated in the recent study of Bi 2 Sr 2 CaCu 2 O 8+δ , where it was found that “the well-known pseudogap feature observed by STM is inherently property of the BiO planes and thus irrelevant directly to Cooper pairing”19. By creating a fresh surface through single-crystal cleavage under ultra-high vacuum, one can study both structural (STM topography) and electronic properties (scanning tunneling spectroscopy (STS)) of the exposed surfaces.…”
mentioning
confidence: 99%